Asia-Pacific news. Issue 2 (April 2016) - Kennedy, Gabriela
Abstract: This column provides a country by country analysis of the latest legal developments, cases and issues relevant to the IT, media and telecommunications industries in key jurisdictions across the Asia Pacific region. The articles appearing in this column are intended to serve as 'alerts' and are not submitted as detailed analyses of cases or legal developments.